An outstanding second-harmonic generation material BiB2O4F: exploiting the electron-withdrawing ability of fluorine. Issue 2 (12th January 2015) - Cong, Rihong; Wang, Ying; Kang, Lei; Zhou, Zhengyang; Lin, Zheshuai; Yang, Tao
Abstract : The fluorine atoms in BiB2 O4 F withdraw the non-bonding electrons of Bi 3+ and thus strongly increase the SHG efficiency. Abstract : It is well known that the incorporation of fluorine usually blue-shifts the absorption edge of a crystal due to its large electronegativity. Herein, we validate the new functionality of fluorine that leads to the strong second harmonic generation (SHG) effect in a unique nonlinear optical (NLO) bismuth borate, BiB2 O4 F, where F coordinates to both B 3+ and Bi 3+ cations. The F-incorporation not only forms a more asymmetric unit [BO3 F] compared to the almost optical isotropic [BO4 ], but also withdraws the non-bonding electrons of Bi 3+, increasing its local polarization; thus the total SHG efficiency is increased significantly. Indeed, experimental measurements and first-principles calculations both support our anticipation that BiB2 O4 F is a phase-matchable NLO material with an exceptionally large SHG response. In order to further consolidate the functionality of fluorine, a comparison study with the structurally similar compound BiB2 O4 (OH) was performed.